Determinación de Sodio, Potasio, Calcio y Cloro en Equinos entrenados para participar en prueba de resistencia - Islas, Armando; Merino M., Victoria; Mora R., Guillermo; Quezada O., Manuel; Kraushaar L., Ricardo; Figueredo X., Mabel (Avances en Ciencias Veterinarias, 2006)
Serum electrolytes and chloride were determined in 12 mixed horses between 6-10 years old in training for endurance competitios.For the determination of sodium, potassium, ionised calcium and chloride blood of jugular vein was obtained after 5 and 6 month of training of the horses. The horses in training were submitted to two test gallop at 360 m/m during 60 minutes. Blood samples in rest conditions, 5 and 15 minutes after exercise were obtained for each test.The results obtained showed that exercise produce a significant decrease of sodium, 5 and 15 minutes post exercise, potassium increased significantly at 5 minutes post exercise. Under exercise for 60 minutes, ionised calcium decrease at 5 and 15 minutes after exercise and chloride decreased significantly at 5 and 15 minutes post exercise.The results obtained showed that exercise for 60 minutes produces more changes in the electrolyte balance this is important to evaluate and to consider to maintain the electrolyte balance.